Transcriptomic changes in the nasal epithelium associated with diesel engine exhaust exposure. (April 2020) - Drizik, E.; Corbett, S.; Zheng, Y.; Vermeulen, R.; Dai, Y.; Hu, W.; Ren, D.; Duan, H.; Niu, Y.; Xu, J.; Fu, W.; Meliefste, K.; et al.
Highlights: Occupational diesel engine exhaust (DEE) exposure alters nasal gene expression. DEE-associated genes have an exposure-response relationship with elemental carbon levels. DEE and cigarette smoke (CS) exposures up-regulate common genes. DEE and CS exposure have a synergistic effect on gene expression. Abstract: Background: Diesel engine exhaust (DEE) exposure causes lung cancer, but the molecular mechanisms by which this occurs are not well understood. Objectives: To assess transcriptomic alterations in nasal epithelium of DEE-exposed factory workers to better understand the cellular and molecular effects of DEE. Methods: Nasal epithelial brushings were obtained from 41 diesel engine factory workers exposed to relatively high levels of DEE (17.2–105.4 μg/m 3 ), and 38 unexposed workers from factories without DEE exposure. mRNA was profiled for gene expression using Affymetrix microarrays. Linear modeling was used to identify differentially expressed genes associated with DEE exposure and interaction effects with current smoking status. Pathway enrichment among differentially expressed genes was assessed using EnrichR. Gene Set Enrichment Analysis (GSEA) was used to compare gene expression patterns between datasets. Results: 225 genes had expression associated with DEE exposure after adjusting for smoking status (FDR q < 0.25) and were enriched for genes in pathways related to oxidative stress response, cell cycle pathways such as MAPK/ERK, protein modification, and transmembrane transport. Genes up-regulated in DEE-exposed individuals were enriched among the genes most up-regulated by cigarette smoking in a previously reported bronchial airway smoking dataset. We also found that the DEE signature was enriched among the genes most altered in two previous studies of the effects of acute DEE on PBMC gene expression. An exposure-response relationship was demonstrated between air levels of elemental carbon and the first principal component of the DEE signature. Conclusions: A gene expression signature was identified for workers occupationally exposed to DEE that was altered in an exposure-dependent manner and had some overlap with the effects of smoking and the effects of acute DEE exposure. This is the first study of gene expression in nasal epithelial cells of workers heavily exposed to DEE and provides new insights into the molecular alterations that occur with DEE exposure.